The analysis of sales and quality management methods in sales strategy and the impact on performance in CV. Tirta Sasmita - Rahman Faisal; Danang Choirul Umam (Journal of Economics and Business Letters, 2021)
CV. Tirta Sasmita is one of the companies engaged in drinking water in the city of South Tangerang. CV. Tirta Sasmita is a new company that is currently issuing the Tirta Sasmita trademark. It is not an easy thing for a new company to compete first in this industry, so that it will affect CV. Tirta Sasmita in determining competitive strategies to survive and develop its business in all respects, such as simplifying the payment system which will affect the power of the company. buy from the drinking water product itself. CV.Tirta Sasmita is not only limited to producing bottled drinking water products, but this company is also engaged in marketing its products. In marketing CV. Tirta Sasmita is one of the companies that sells on consignment. CV Tirta Sasmita can provide fresh air for the Foundation in particular and the community in general, by contributing to increasing the income of the surrounding community by becoming an agent for mineral water products using a consignment sales system. This study examines and analyzes the influence of sales methods and quality management on sales strategies and their impact on company performance. Data were obtained from customers and agents through questionnaires, the data were then analyzed using descriptive quantitative methods, with the help of SmartPLS 3.0 software. Based on the research results, the sales method variable has a positive and significant effect on sales strategy, the management quality variable has a positive and significant effect on sales strategy, while the sales strategy has no effect on organizational performance.